Three-year review of a capacity building pilot for a sustainable regional network on food, nutrition and health systems education in India. Issue 1 (1st February 2021) - Buckner, Luke; Carter, Harrison; Ahankari, Anand; Banerjee, Rinku; Bhar, Somnath; Bhat, Shivani; Bhattacharya, Yagnaseni; Chakraborty, Debashis; Douglas, Pauline; Fitzpatrick, Laura; Maitra-Nag, Sudeshna; Muhkerjee, Sagarika; et al.
Abstract : Background: In Kolkata (India), there are high rates of malnourished children (45.9%) under the age of three, impacting growth, organ development, function, and cognition. Mothers have a major role to play during this crucial development stage, with research showing nutrition knowledge, attitudes and practices (KAP) of mothers are important determinants of childhood malnutrition. Aims: To document 3 years of capacity building towards a sustainable nutrition education network in Kolkata, India, while assessing the ability to perform data collection in the form of needs assessments, impact assessments and capacity reviews. Methods: Descriptive review and analysis of engagement and impact from 3 years of work by the NNEdPro Global Centre for Nutrition and Health, initiating locally led nutrition education interventions. Mapping to the Indian National Nutrition Strategy was also performed to review adherence to nationwide priorities surrounding nutrition and determine the wider application potential of the network. Results: Two simultaneous projects were taken forward by a team of local healthcare professionals and student champions. Project 1—medical college workshops for medical student nutrition education with added focus on underserved populations, Project 2—preparation for a 'Mobile Teaching Kitchen' (MTK) in marginalised communities to empower local women as nutrition educators. Data collection methods used for analysing markers of impact and sustainability were semi-structured interviews of the community members, and KAP questionnaires to assess response to educational sessions. Conclusion: With local support it is possible to create and sustain fieldwork for an extended period with meaningful outputs and impact. This initiative demonstrates that it is possible to use healthcare professionals, students and volunteers with low-intensity training and a low-cost approach to produce action research with considerable impact and results in rapid, reliable and robust manner.